2022
DOI: 10.3390/antibiotics11091244
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Trends and Antibiotic Susceptibility Patterns in Patients with Periprosthetic Joint Infection of the Hip or Knee over 6 Years

Abstract: We sought to analyze trends of the causative pathogens and their antibiotic susceptibility patterns in patients with periprosthetic joint infections (PJI) of the hip and knee to get better insights and improve treatment. Retrospective evaluation of all consecutive patients with microbiological detection of a causative pathogen at a tertiary endoprothetic referral center between January 2016 and December 2021 in Germany was performed. Overall, 612 different microorganisms could be detected in 493 patients (hip:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Rifampicin is one of the most important drugs used in the treatment of PJI; thus, resistance to rifampicin is a threat to the management of PJI. Fröschen et al [21] reported a stable average rifampicin resistance per year of 24.4% in PJIs caused by CoNS in the last 6 years (2016-2021) in Germany. Contrary to these results and the global trend of increasing antibiotic resistance, we found a decreasing trend of PJIs caused by rifampicin-resistant bacteria in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Rifampicin is one of the most important drugs used in the treatment of PJI; thus, resistance to rifampicin is a threat to the management of PJI. Fröschen et al [21] reported a stable average rifampicin resistance per year of 24.4% in PJIs caused by CoNS in the last 6 years (2016-2021) in Germany. Contrary to these results and the global trend of increasing antibiotic resistance, we found a decreasing trend of PJIs caused by rifampicin-resistant bacteria in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Given the pivotal role of rifampicin in PJI treatment and the concerning rise in rifampicin resistance in recent decades, it has become imperative to address this issue [69,70]. A study outlining the occurrence of rifampicin-resistant bacteria isolated from PJI patients reported a consistent 24% level of rifampicin resistance in PJI-associated bacteria over a 6-year period [71]. In contrast, a more recent study spanning two decades at our unit unveiled a declining trend in PJIs caused by rifampicin-resistant bacteria when comparing the time frames of 2011-2015 and 2016-2020 [67].…”
Section: Discussionmentioning
confidence: 99%